Host poly(ADP-ribose) polymerases (PARPs) in acute and chronic bacterial infections - Moona Miettinen; Madhukar Vedanthama; Arto T. Pulliainen (Elsevier Masson SAS, 2022)
Abstract
Protein ADP-ribosylation is a reversible post-translational modification, which alters protein activity, localization, interactome or stability, leading to perturbation of cell signaling. This review summarizes the emerging data indicating that host cell ADP-ribosylating enzymes, poly(ADP-ribose) polymerases (PARPs), influence the course of a bacterial infection, in parallel to ADP-ribosylating bacterial toxins. Host cell PARP targeting could be an efficient therapeutic approach to treat certain bacterial infections, possibly by repurposing the approved or clinical trial PARP inhibitors developed for cancer therapy.